2005
DOI: 10.1590/s1415-47572005000400019
|View full text |Cite
|
Sign up to set email alerts
|

Identification and frequency of transposable elements in Eucalyptus

Abstract: Transposable elements (TE) are major components of eukaryotic genomes and involved in cell regulation and organism evolution. We have analyzed 123,889 expressed sequence tags of the Eucalyptus Genome Project database and found 124 sequences representing 76 TE in 9 groups, of which copia, MuDR and FAR1 groups were the most abundant. The low amount of sequences of TE may reflect the high efficiency of repression of these elements, a process that is called TE silencing. Frequency of groups of TE in Eucalyptus lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…In Saccharum officinarum , out of 260,781 ESTs, 276 (0.1%) were considered to be expressed TEs [38] . Finally, in Eucalyptus grandis , out of 123,889 ESTs, 124 (0.1%) were identified as transcriptionally active TEs [39] . Our data reinforce the fact that TEs are poorly represented in the Coffea transcriptome, although plant genomes are enriched by those repetitive sequences.…”
Section: Discussionmentioning
confidence: 99%
“…In Saccharum officinarum , out of 260,781 ESTs, 276 (0.1%) were considered to be expressed TEs [38] . Finally, in Eucalyptus grandis , out of 123,889 ESTs, 124 (0.1%) were identified as transcriptionally active TEs [39] . Our data reinforce the fact that TEs are poorly represented in the Coffea transcriptome, although plant genomes are enriched by those repetitive sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, TE dynamics were scarcely studied in the Eucalyptus genus and most analysis were based on private EST data [i.e. [ 14 ]. In the present study, we identify and comprehensively characterize a selected group of Eucalyptus LTR-RTEs, emphasizing the characterization of elements with putative transcriptional activity.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 10 years, an abundance of experimental evidence has accumulated that directly points to the contribution of transposable elements (TEs) to host gene structure, function and expression (Britten, 1996a(Britten, ,b, 1997(Britten, , 2004Nekrutenko and Li, 2001;Landry et al, 2001Landry et al, , 2002Landry and Mager, 2003;Sorek et al, 2002;Jordan et al, 2003;Lorenc and Makalowski, 2003; Van de Lagemaat et al, 2003;Jordan et al, 2003;Boeke, 2004, 2005;Bacci et al, 2005;Dunn et al, 2005Dunn et al, , 2006DeBarry et al, 2005;Ganko et al, 2003;Ganko, 2006). These studies also have shown that the evolutionary consequences of TE insertions in the host genome are diverse when they occur within genes.…”
Section: Introductionmentioning
confidence: 99%